The Application of Chaotic Dynamics to Epidemiological and Biomedical Problems. - Vitale, Joseph (1995)
Keywords: dept.csc; faculty_collection; sabbatical_report

Texture analysis of ultrasonic images using backpropagation neural networks - Parikh, Jo Ann; Daponte, John S; Damodaran, Meledath (International Conference on Semantic Computing, 1995)
Backpropagation neural networks are applied to the problem of characterization of ultrasonic image texture to detect abnormalities in tissue texture which are indicative of liver disease. Twenty-one texture features were extracted from regions of interest in digitized ultrasonic images. A feature subset, identified by a stepwise selection process, formed the sample input to the networks together with the physician-supplied diagnosis. The classification performance of the backpropagation network is evaluated using a jackknife testing procedure. The performance of the networks is compared with results obtained from linear discriminant analysis and logistic regression techniques. © Springer-Verlag Berlin Heidelberg 1995.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Back propagation neural networks; Backpropagation; Backpropagation network; Classification performance; Computer graphics; Diagnosis; Discriminant analysis; Image analysis; Image texture; Linear discriminant analysis; Logistic regressions; Neural networks; Regions of interest; Testing procedure; Texture analysis; Ultrasonic applications; Ultrasonic imaging; dept.csc

Pancreatic cancer among workers processing synthetic resins - Selenskas, Sandra; Teta, M Jane; Vitale, Joseph N (American Journal of Industrial Medicine, 1995)
A nested case‐control study was conducted to investigate whether an excess of pancreatic cancer, identified in a cohort mortality study with follow‐up from 1946 through 1988. was associated with potential workplace exposures at a New Jersey plastics manufacturing and research and development facility. The study population included 28 male pancreatic cancer cases and 140 randomly selected controls, matched on year of birth and at risk (alive) at the time of the case death. Using plant work history records, department assignments for the two groups were compared according to duration and time since first assignment. Workers assigned to a work area that processed vinyl resins and polyethylene (PE) were shown to be at increased risk. Men assigned more than 16 years to this department had a significantly increased risk ratio of 7.15 (95% confidence intervals [CI]: 1.28–40.1). No excess was seen with shorter duration assignments. Seven of the nine cases began working in this area in the 1940s. Average latency was 32 years, and all but three cases worked 20 years or more in this unit. Over the study period, significant exposure‐related process changes occurred, in addition to the use of numerous chemical additives. Although vinyl and PE processing operations could not be analyzed separately, the pancreatic cancer excess is more likely to be related to vinyl processing. Identification of a causative agent or combination of agents would require investigations with more detailed exposure information. Copyright © 1995 Wiley Periodicals, Inc., A Wiley Company
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-244-367-871-530 tex.type: [object Object]
Keywords: Aged; Aged; 80 and over; Case-Control Studies; Cohort Studies; Human; Male; Middle Age; Occupational Diseases; Pancreatic Neoplasms; Polyethylenes; Risk Factors; Time Factors; Vinyl Compounds; adult; aged; article; cancer mortality; cancer risk; case control study; case‐control study; controlled study; dept.csc; diethylhexyl phthalate; female; human; industry; major clinical study; male; occupational cancer; occupational exposure; occupational hazard; pancreas cancer; pancreatic neoplasm; plasticizer; plastics; polyethylene derivative; polyvinyl chloride; vinyl derivative